2011
DOI: 10.1124/jpet.110.178236
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nicotinic Acetylcholine Receptor Protein Underlies Chronic Nicotine-Induced Up-Regulation of Nicotinic Agonist Binding Sites in Mouse Brain

Abstract: Chronic nicotine treatment elicits a brain region-selective increase in the number of high-affinity agonist binding sites, a phenomenon termed up-regulation. Nicotine-induced up-regulation of ␣4␤2-nicotinic acetylcholine receptors (nAChRs) in cell cultures results from increased assembly and/or decreased degradation of nAChRs, leading to increased nAChR protein levels. To evaluate whether the increased binding in mouse brain results from an increase in nAChR subunit proteins, C57BL/6 mice were treated with nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
66
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 34 publications
15
66
1
Order By: Relevance
“…No associations between a 4 b 2 * nAChR densities and treatment type were found, but significant associations were discovered between the extent of a 4 b 2 * nAChR density reduction and the amount of decreased cigarette usage. These results indicate that a 4 b 2 * nAChR density is strongly linked to the number of cigarettes smoked per day, but not to the treatment type being administered, and are consistent with our previous study of untreated smokers (Brody et al, 2013) and other studies linking nicotine (Marks et al, 2011;Yates et al, 1995;Zhang et al, 2002) and cigarette smoke (Mamede et al, 2007;Mukhin et al, 2008;Staley et al, 2006;Wullner et al, 2008) exposure with upregulation of a 4 b 2 * nAChRs in brain regions other than the thalamus. Because education about the biological effects of smoking and quitting smoking are standard parts of smoking-cessation psychotherapy (Fiore et al, 2008), the additional information found here could prove useful in treatment of smokers by letting them know that brain receptor changes found with regular smoking tend toward normalization with smoking reduction and cessation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…No associations between a 4 b 2 * nAChR densities and treatment type were found, but significant associations were discovered between the extent of a 4 b 2 * nAChR density reduction and the amount of decreased cigarette usage. These results indicate that a 4 b 2 * nAChR density is strongly linked to the number of cigarettes smoked per day, but not to the treatment type being administered, and are consistent with our previous study of untreated smokers (Brody et al, 2013) and other studies linking nicotine (Marks et al, 2011;Yates et al, 1995;Zhang et al, 2002) and cigarette smoke (Mamede et al, 2007;Mukhin et al, 2008;Staley et al, 2006;Wullner et al, 2008) exposure with upregulation of a 4 b 2 * nAChRs in brain regions other than the thalamus. Because education about the biological effects of smoking and quitting smoking are standard parts of smoking-cessation psychotherapy (Fiore et al, 2008), the additional information found here could prove useful in treatment of smokers by letting them know that brain receptor changes found with regular smoking tend toward normalization with smoking reduction and cessation.…”
Section: Discussionsupporting
confidence: 80%
“…Human postmortem tissue studies show that chronic smokers have increased numbers of a 4 b 2 * nAChRs compared with non-smokers (Benwell et al, 1988;Breese et al, 1997) and that former smokers (41 year abstinent) have nAChR densities similar to nonsmokers (Breese et al, 1997). Many laboratory animal studies also demonstrate upregulation of nAChRs in response to chronic nicotine administration (eg, Marks et al, 2011;Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Future experiments are clearly warranted to identify this fifth subunit because auxiliary subunits can play an important role in determining agonist sensitivity and calcium permeability (Gerzanich et al, 1998;Brown et al, 2007;Sciaccaluga et al, 2015). Combined approaches using selective immunoprecipitation, radioligand binding, and immunohistochemistry may be particularly helpful in this regard (Whiteaker et al, 2000;Gotti et al, 2005;Grady et al, 2009;Lomazzo et al, 2010;Marks et al, 2011). Fig.…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…Moreover, the area postrema is endowed with heteromeric ␣3␤4 nAChRs, which modulate inhibitory GABAergic transmission (Kawa, 2007). The following observations demonstrate that the interaction of nicotine with nAChRs varies depending on receptor, gender, and hormonal profiles: 1) the medullary expression of ␣7 and ␤2 nAChRs is decreased and increased, respectively, by nicotine (Browne et al, 2010), 2) nicotine increases ␣4␤2 nAChR binding sites in mouse brain (Marks et al, 2011), 3) compared with males, nicotine-treated females have higher medullary ␤2 nAChRs (Browne et al, 2010), and 4) estradiol increases ␣7 nAChRs in dorsal raphe and locus coeruleus neurons (Centeno et al, 2006). More studies are obviously needed to determine the relative contributions of central nicotinic receptors in the gender and hormonally dependent nicotine-baroreflex interaction.…”
Section: Discussionmentioning
confidence: 96%